Financial reform and financial sector development in Jamaica. - PEART, Kenloy (1995)
Analyses Jamaica's financial system in the period prior to the programme of structural adjustment which was initiated in the early 1980's. Discusses the financial reform programme and provides a preliminary assessment of its impact.